2018
DOI: 10.1177/0886260518767900
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Rural Elders in Mansoura Districts, Dakahlia, Egypt: Prevalence, Types, Risk Factors, and Lifestyle

Abstract: This study was carried out to explore the prevalence of elderly abuse, identify its types, associated risk factors and determine quality of their life in Rural Mansoura districts, Egypt. A cross-section study was conducted on a sample of 272 elders recruited from outpatient clinicsFamily Health Centers in Shawa & Berkin villages from May 1 to September 3, 2016. 200 (73.5%) elders accepted participation. A previously designed and validated questionnaires were used to collect data from participants. 46% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
(11 reference statements)
3
11
1
Order By: Relevance
“…In addition, the literature shows that older adults with a high number of comorbidities have a higher chance of suffering violence (44) . Reinforcing this analysis, a study developed in Dakahlia, Egypt, with 272 older adults concluded, based on the regression analysis, that having no chronic comorbidities is a protective factor for older adult women (45) .…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the literature shows that older adults with a high number of comorbidities have a higher chance of suffering violence (44) . Reinforcing this analysis, a study developed in Dakahlia, Egypt, with 272 older adults concluded, based on the regression analysis, that having no chronic comorbidities is a protective factor for older adult women (45) .…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, in studies conducted in Turkey, income less than expenses is one of the factors that increase the risk of exposure to abuse (Ergin et al, 2012;Kulakçı Altıntas & Korkmaz Aslan, 2019). Elderly people, who are vulnerable to external effects, have a higher need for caregivers, especially when they are dependent on others, when they have mental problems and/or when they cannot meet their needs (El-Khawaga et al, 2018;Friedman et al, 2017;Keller et al, 2019), which may affect their relationship with their caregiver and increase the risk of exposure to abuse (James, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The form developed by the researcher includes 11 items questioning the participants' sociodemographic characteristics such as age, sex, education level, income level, and their health-related characteristics such as the presence of a chronic disease, sleep problems (Arab-Zozani et al, 2018;El-Khawaga et al, 2018;Ergin et al, 2012).…”
Section: Personal Information Formmentioning
confidence: 99%
See 2 more Smart Citations